2014
DOI: 10.1111/ppa.12216
|View full text |Cite
|
Sign up to set email alerts
|

An isolate morphologically and phylogenetically distinct from Botrytis cinerea obtained from withered grapes possibly represents a new species of Botrytis

Abstract: Grapes kept after harvest for withering in drying fruit rooms (fruttaio) are highly susceptible to Botrytis cinerea infection. A taxonomically undefined isolate (B83) was identified during a survey of B. cinerea populations in these specific environments. This isolate yielded negative results in B. cinerea-specific PCRs and displayed a different colony morphology on potato dextrose agar. Based on this data, the isolate underwent a taxonomic investigation. Sequencing of the ITS-5Á8S-ITS2 region indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
(81 reference statements)
1
19
0
1
Order By: Relevance
“…Clade I includes the isolates from group I and II species B. californica , B. calthae , B. cinerea , B. eucalypti , B. fabae , B. pelargonii , B. pseudocinerea and B. sinoviticola . Recently, a new clade II Botrytis species, B. euroamericana , was found on grapevine in Italy (Lorenzini & Zapparoli, ; Garfinkel et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Clade I includes the isolates from group I and II species B. californica , B. calthae , B. cinerea , B. eucalypti , B. fabae , B. pelargonii , B. pseudocinerea and B. sinoviticola . Recently, a new clade II Botrytis species, B. euroamericana , was found on grapevine in Italy (Lorenzini & Zapparoli, ; Garfinkel et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have shown that B. cinerea exists within a morphologically cryptic species complex (Giraud et al, 1997(Giraud et al, , 1999Albertini et al, 2002;Fournier et al, 2003Fournier et al, , 2005Walker et al, 2011;Lorenzini & Zapparoli, 2014;Liu et al, 2016;Garfinkel et al, 2017). Distinguishing different Botrytis species in sympatry and defining their contributions to disease could assist in adapting control strategies (Walker, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA from pure cultures of the nine isolates was extracted according to Lorenzini and Zapparoli (). Restriction fragment length polymorphism (RFLP) of the internal transcribed spacer (ITS) region of the rDNA using the primers ITS1 and NL4 was performed on nine isolates as described by Alves et al .…”
Section: Methodsmentioning
confidence: 99%
“…This Lorenzini and Zapparoli, 2014;Walker et al, 2011;Zhou et al 2014). Similarly, phylogenetic analysis suggests the presence of cryptic species in B. cinerea from stone fruits in Chile (Ferrada et al, 2014).…”
Section: The Pathogenmentioning
confidence: 99%